Pro-Fibrotic CD26-Positive Fibroblasts Are Present in Greater Abundance in Breast Capsule Tissue of Irradiated Breasts. (11th April 2019) - Borrelli, Mimi R; Irizzary, Dre; Patel, Ronak A; Nguyen, Dung; Momeni, Arash; Longaker, Michael T; Wan, Derrick C
Abstract: Background: Breast capsular contracture is a major problem following implant-based breast reconstruction, particularly in the setting of radiation therapy. Recent work has identified a fibrogenic fibroblast subpopulation characterized by CD26 surface marker expression. Objectives: This work aimed to investigate the role of CD26-positive fibroblasts in the formation of breast implant capsules following radiation therapy. Methods: Breast capsule specimens were obtained from irradiated and nonirradiated breasts of 10 patients following bilateral mastectomy and unilateral irradiation at the time of expander-implant exchange, under institutional review board approval. Specimens were processed for hematoxylin and eosin staining as well as for immunohistochemistry and fluorescence activated cell sorting for CD26-positive fibroblasts. Expression of fibrotic genes and production of collagen were compared between CD26-positive, CD26-negative, and unsorted fibroblasts. Results: Capsule specimens from irradiated breast tissue were thicker and had greater CD26-postive cells on immunofluorescence imaging and on fluorescence activated cell sorting analysis than did capsule specimens from the nonirradiated breast. Compared with CD26-negative fibroblasts, CD26-positive fibroblasts produced more collagen and had increased expression of the profibrotic genes IL8, TGF-β1, COL1A1, and TIMP4. Conclusions: CD26-positive fibroblasts were found in a significantly greater abundance in capsules of irradiated compared with nonirradiated breasts and demonstrated greater fibrotic potential. This fibrogenic fibroblast subpopulation may play an important role in the development of capsular contracture following irradiation, and its targeted depletion or moderation may represent a potential therapeutic option. Level of Evidence: 2: